2019
DOI: 10.3389/fpls.2019.01488
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ABA Receptor PYL10 Gene Confers Drought and Cold Tolerance to Indica Rice

Abstract: Abscisic acid (ABA) plays versatile functions in regulating plant development and tolerance to various biotic and abiotic stresses. Towards elucidating the functions of one of the ABA receptors (ABARs) in rice, OsPYL10 was cloned from drought tolerant rice cv. Nagina 22 and was overexpressed under stress inducible RD29A promoter in a mega rice variety MTU1010 by using Agrobacterium mediated genetic transformation. Four single copy transgenic lines selected based on Southern blot analysis were used for physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 64 publications
3
41
0
Order By: Relevance
“…Nagina 22. In a previous study, OsPYL10 [47] expression was found to be downregulated by PEG, NaCl and cold stresses in the roots, but was found to be upregulated by ABA in roots. In this study also similar expression of OsPYL10 was found under these treatments.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 81%
See 3 more Smart Citations
“…Nagina 22. In a previous study, OsPYL10 [47] expression was found to be downregulated by PEG, NaCl and cold stresses in the roots, but was found to be upregulated by ABA in roots. In this study also similar expression of OsPYL10 was found under these treatments.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 81%
“…Previous functional validation studies have shown that constitutive/stress-inducible overexpression of OsPYL2 [42], OsPYL10 [42,47,87], and OsPYL11 (=RCAR5) [44] conferred tolerance to abiotic stresses. In a previous study, expression analysis of OsPYL11 (=RCAR5) [44] under salt, PEG and ABA treatments showed that it is significantly downregulated by ABA and salt stress.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The essential roles of ABA and JA in plant stress responses and stress tolerance provide important clues for the development of stress-tolerant plants, and many successful studies reported stress-tolerant crops generated by modulation of ABA or JA responses. For example, activation or overexpression of OsPYL10, an ABA receptor increased ABA responses, leading to improved tolerance to drought [8], and overexpression of OsbZIP42 or heterologous expression of ZmbZIP4 (encoding positive regulators of ABA signaling) conferred drought tolerance in rice [9,10]. Additionally, a knock-out of the JA signaling repressor OsJAZ1 increased JA sensitivity and drought tolerance; conversely, overexpression of OsJAZ1 reduced JA sensitivity and drought tolerance [11].…”
Section: Introductionmentioning
confidence: 99%